Association of serum Vitamin D and salivary calcium and phosphorus levels in 3-11-year-old schoolchildren with dental caries - N Pratyusha; C Vinay; K S Uloopi; Kakarla Sri RojaRamya; P Ahalya; Chigurupati Devi (Wolters Kluwer Medknow Publications, 2021)
Background: Vitamin D plays an essential role in the formation of healthy teeth, protection against dental caries, and the appropriate secretion of salivary calcium. Salivary calcium and phosphate help in maintaining equilibrium between demineralization and remineralization of teeth. If we know the association between serum Vitamin D and salivary calcium and phosphorus, we may get a clue regarding serum Vitamin D levels which in turn is essential for good oral health. Aim: The aim of this study was to assess the association of serum Vitamin D levels and salivary calcium and phosphorus levels in children with dental caries. Settings and Design: This was a comparative cross-sectional study. Materials and Methods: One hundred children of age 6-11 years, 50 with Decayed, Missing, and Filled Teeth (DMFT) ≥5 (test group) and 50 with DMFT = 0 (control group), were included in the study. Oral examination was carried out and DMFT/deft scores were recorded. Serum 25-hydroxy Vitamin D levels and salivary calcium and phosphorous levels were measured. Statistical Analysis: Independent sample t-test, linear regression analysis, and Pearson correlation test were used for statistical analysis. Results: Children with dental caries have shown lesser mean serum Vitamin D levels (15.37 ± 3.53) than caries-free children (17.26 ± 3.16). Children with decayed teeth have exhibited lower salivary calcium levels (3.92 ± 0.99) than those without caries (4.42 ± 1.37). Conversely, children with dental caries have shown higher mean salivary phosphate levels (6.27 ± 1.74) than caries-free children (5.18 ± 1.47). There is a significant decrease in salivary calcium (P = 0.018) and serum Vitamin D (P = 0.004) with a significant increase in number of decayed teeth. The greater the Vitamin D deficiency, the lesser are the salivary calcium levels observed (P = 0.001). Conclusions: Children with Vitamin D deficiency have lower salivary calcium levels. Vitamin D deficiency and lower salivary calcium levels can be the potential risk factors for the occurrence of dental caries.